“Proyecto De Factibilidad Para La Implementación De Una Empresa Productora Y Comercializadora De Chocolates En La Ciudad De Loja - Sánchez Ruiz, Lenin Oswaldo (2016)
At the moment the city of Loja is affected by a notorious recession in the productive field, being a barrier for its sustained development that doesn't allow competing with other counties of the country. The present investigative work tries on the creation and elaboration of a proposal for the implementation of a company producer and commercialization of Chocolates in the city of Loja. It is so the ready investigation all the steps and studies that you/they help to define the effectiveness of the project. For these reasons this project has as purpose to help with the implementation of a company that allows to create some work sources, take advantage of the natural existent resources, creating a value economic attaché and to apply the acquired knowledge, in benefit of a society that he/she needs its new professionals to be inserted in the productive and economic life. Of here the real necessity to produce goods and services, being venturesome and confronting the serious crisis that crosses our country, being convenient to carry out and to execute the denominated thesis project: "PROJECT OF FEASIBILITY FOR THE IMPLEMENTATION OF A COMPANY PRODUCER AND COMERCIALIZADORA OF CHOCOLATES IN THE CITY DE LOJA", the same one that contributes to the development of this city. The complete analysis of the project requires of the realization of the objectives proposed as first objective the market study is it analyzes the offer and the demand. For all these he/she was carried out a survey so much to plaintiffs as officers, it stops then to determine the unsatisfied demand that is of 664272 pounds for the first year, the installed capacity it was determined that it is of 100% and the used capacity of the project is of 83,33 alone% for the first year. In the organizational study of the company, some legal and organic aspects were determined that it is required for a normal operation like they are: their mission, vision, social capital, the company type, their hierarchical levels and the manual of functions. The company will develop its economic activities under the social reason "CHOCOLIC" Co.. Ltda. With their respective flowcharts and the mission will be to take place and to market natural chocolate, to satisfy with quality and competitive prices the demand of the city of Loja.I study economic and financier to know on the investment of the project (investment in active fixed, differed and work capital), financing of the investment, budget of revenues and expenditures, analysis of costs, balance points and study and analysis of the financial (state of losses and Earnings and the box flow) states. Finally he/she was carried out the evaluation of the project to establish the convenience of the project and of their execution for that reason was analyzed the following indicators as the Current Net Value of $170523,07; It Appraises It Interns of Return of 89,01%; Relationship Benefits Cost it is of 1,30 for each invested dollar the company it wins 0,30 cents; Period of Recovery of Capital is of 1 year, 11 months and 12 days; Analysis of Sensibility indicates that the project supports an increment in the costs of 16,68% giving a total of 0,98% and the analysis of sensibility in the decrease in the revenues of 12,69% giving a total of the one 0.99% reason why the project is feasible whose conclusions and recommendations determine this way it, the bibliography consulted with their respective annexes being attached.